Marketing underutilized crops: the case of the African garden egg (Solanum ethiopicum) in Ghana - Horna, D.; Timpo, S.; Gruère, G. (2007)
The overall objective of this study is to analyze constraints affecting the African garden egg market chain in Ghana. Furthermore, to identify the factors that help determine the success of market chain development of garden egg in Ghana; and to analyze the effect of market development on biodiversity.